2020
DOI: 10.1021/acs.jafc.0c05553
|View full text |Cite
|
Sign up to set email alerts
|

Feruloylated Oligosaccharides Alleviate Central Nervous Inflammation in Mice Following Spinal Cord Contusion

Abstract: As one of the empirical models of the chronic central inflammatory response, a spinal cord injury (SCI) deteriorates the neuronal survival and results in irreversible motor and sensory dysfunction below the injury area. Our previous studies have reported that maize bran feruloylated oligosaccharides (FOs) exert significant anti-inflammatory activities both in diabetes and colitis. However, no direct evidence of FOs alleviating central nervous inflammation was stated. This study aimed to investigate the therape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 57 publications
(75 reference statements)
0
5
0
Order By: Relevance
“…After ingestion, FOs manifest shared biological effects derived from both components. Our prior research has shown that FOs have the ability to reduce inflammation by blocking the release of IL-23 and IL-6, while also boosting the release of TGF-β1 in dendritic cells. Furthermore, our research indicated that FOs decreased the quantity of microglia in case of neuroinflammation, resulting in the suppression of IL-1α, IL-2, IL-6, IL-18, and TNF-α in the central nervous system (CNS) . These collective findings suggest that FOs have anti-inflammatory effects.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…After ingestion, FOs manifest shared biological effects derived from both components. Our prior research has shown that FOs have the ability to reduce inflammation by blocking the release of IL-23 and IL-6, while also boosting the release of TGF-β1 in dendritic cells. Furthermore, our research indicated that FOs decreased the quantity of microglia in case of neuroinflammation, resulting in the suppression of IL-1α, IL-2, IL-6, IL-18, and TNF-α in the central nervous system (CNS) . These collective findings suggest that FOs have anti-inflammatory effects.…”
Section: Introductionmentioning
confidence: 55%
“…The elution gradient was set up with the following parameters: 0 to 5 min, A:B = 90:10 (v/v); 5.1 to 20 min, A:B = 75:25; 20.1 to 25 min, A:B = 68:32; and 25.1 to 35 min, A:B = 90:10 . The flow rate remained constant at 0.3 mL/min, with the column temperature set at 23 °C. , ESI-positive or -negative ions (H + ) were employed for determining the molecular weight of the compounds present in the hydrolysates. , Moreover, the method for detecting the concentration of conjugated FA in FOs has been extensively applied in several previous studies conducted by our research team. , FOs species were identified through HPLC-MS or MS, with monosaccharides analyzed using an ion chromatograph . The average polymerization degree (DP) was calculated by dividing the total sugar content by the reducing sugar content.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…FOs modulated the expression of inflammatory mediators (downregulated TNF-α, IL-2, IL-6, IL-18 levels, and upregulated IL-10 and BDNF) and ameliorated behavioral recovery following spinal cord injury. Furthermore, the study demonstrated that FOs exhibited anti-inflammatory and neuroprotective effects via the mitogen-activated protein kinase signaling pathway with enhanced expression of BDNF levels ( Li et al, 2020 ).…”
Section: Therapeutic Spectrum Of Prebiotic Oligosaccharides and Their Neuroprotective Effect: Validated Experimental Evidence On Probablementioning
confidence: 99%
“…COS can be isolated from natural sources or can be produced by chitin hydrolysis using chitinase ( Ahmed et al, 2012 ; Qin and Zhao, 2019 ). Recently, the neuroprotective properties of feruloylated oligosaccharides (FOs) from maize bran have been evaluated ( Li et al, 2020 ).…”
Section: Introduction To Prebiotics and Its Typesmentioning
confidence: 99%